Serum CD44 Variant 6 to CD44 Ratio and Vascular Endothelial Growth Factor Levels as Predictors of Metastasis in Luminal Subtype Breast Cancer - Ni Putu Yenny Kendarini; Ida Bagus Tjakra Wibawa Manuaba; I Wayan Sudarsa; Tjokorda Gde Bagus Mahadewa; Ni Nyoman Ayu Dewi; Prayuda Prayuda; Putu Febry Krisna Pertiwi (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Metastasis is the leading cause of mortality in luminal subtype breast cancer. While cluster of differentiation (CD)44 has been widely studied, the prognostic relevance of its isoforms particularly the CD44v6/CD44s ratio remains unclear. This study evaluates CD44v6, CD44s, vascular endothelial growth factor (VEGF), and the CD44v6/CD44s ratio as potential prognostic biomarkers for metastasis in luminal breast cancer.METHODS: This case-control study included 38 luminal subtype breast cancer patients (18 with metastasis, 20 without metastasis). Serum levels of CD44v6, CD44s, VEGF, and the CD44v6/CD44s ratio were measured using Enzyme-Linked Immunosorbent Assay (ELISA). Statistical analyses included ROC analysis to determine optimal cut-off points, logistic regression to assess risk factors, and correlation analysis for biomarker relationships.RESULTS: A low CD44v6/CD44s ratio (<0.03) was identified as a significant independent factor for metastasis (adjusted OR 7.0, 95% CI: 1.2–40.6, p=0.03). While serum levels of CD44v6, CD44s, and VEGF were higher in the metastasis group, these individual markers showed a non-significant trend toward association with metastasis. A strong positive correlation was observed between CD44s and VEGF levels (r=0.7, p<0.01).CONCLUSION: The CD44v6/CD44s ratio showed a significant association with metastasis and may have potential as a prognostic marker in luminal breast cancer. Further studies with larger sample sizes are needed to confirm these findings.KEYWORDS: CD44v6, CD44s, VEGF, CD44v6/CD44s ratio, luminal breast cancer, metastasis